Teachers’ knowledge of higher order thinking and questioning skills: A case study at primary school in Terengganu, Malaysia - Wan Yusoff, Wan Mazwati; Che Seman, Shamilati (Human Resource Management Academic Research Society, 2018)
The purpose of this research was to explore primary school teachers’ knowledge of higher order thinking (HOTS) and questioning skills. This was done because little is known about the level of teachers’ knowledge and skills in HOTS; and their knowledge and skills in questioning to stimulate HOTS. To this end this paper employed exploratory case study to gain an in-depth understanding of this phenomenon in the actual setting so that the actual behaviour can be examined with minimum interference that may obstruct the reality. Nine primary school teachers were selected to be interviewed and observed. Semi-structured interview questions were used to collect data on teachers understanding of the concept of thinking and higher order thinking skills; and Likert- type checklist was used to gather data on the frequencies and types of questions teachers usually asked to promote thinking. Observations were conducted to validate the teachers’ responses regarding the frequencies and types of questions asked during teaching and learning sessions. The data gathered through interviews were analysed to determine the emerging themes. The findings revealed that the teachers failed to explain clearly the concept of thinking and thinking processes; and majority of teachers could not give satisfactory explanation of HOTS as critical and creative thinking. However, half of the teachers could list the subskills of HOTS according to Bloom’s Taxonomy. Data on teachers’ questioning skills revealed that they were familiar with questioning based on Bloom’s Taxonomy, however only half of the teachers practised asking HOTS questions based on Bloom’s Taxonomy.